Modeling of the vane test using a power-law fluid and model order reduction techniques: application to the identification of cement paste properties - Ghnatios, Chady; Zéhil, Gérard-Philippe; Habchi, Charbel (Comptes rendus. Mecanique, 2021)
The effective modeling of fresh cementitious materials during setting is an active and challenging research topic. The material behavior as well as the parameters and properties are not fully understood yet. Therefore, the flow during casting is the subject of ongoing research. Previous works attempted to model cement paste as a solid subjected to yielding, or as a fluid modeled by a Brinkman law or a power law, both in 2D or 3D. Of existing models, 3D simulation of power-law fluids seems to carry the best predictive abilities, considering the shear-thinning behavior of the cement paste. In this work, we model the vane test of cement paste using a power-law pseudoplastic fluid. We also add all material and model parameters as extra coordinates of the problem, an appealing approach when identifying material properties, at the expense of increasing the problem’s dimensionality and computational time, often referred to as the combinatory explosion. However, using model order reduction techniques, we have the ability to circumvent the curse of dimensionality by solving a full-scale multidimensional problem as a sequence of lower dimensionality problems. In what follows, we use the Proper Generalized Decomposition (PGD) to solve a multidimensional (6D) nonlinear power-law fluid problem and identify the cement paste properties.